Development of modified sliding mode control of the LCC series-parallel resonant converter based on frequency variation - Halivor, James; Chenguang, Yang; Ying, Feng (Open Science Journal, 2023)
This paper discusses the elements of high frequency power supplies and high voltages which are used considerably in high voltage applications, for industrial applications, atmospheric pressure plasma processing, X-ray high voltage applications, electrostatic precipitation, etc. For this reason, the LCC criteria presents a reliable option incorporated in its topology, which makes upmost use of leakage inductance and convoluting capacitance to remove the negative effects of converter operation. These render it a viable choice in most power and energy applications. The LCC Series-Parallel Resonant Converter adopts the desirable properties of both the parallel and series resonant converter which include reduced peak currents, miniature variations in switching frequency and high efficiency. Sliding Mode Control (SMC) is a satisfactory robust control technique suitable for a specific array of nonlinear systems. Sliding mode approach is able to disregard certain anomalies and irregularities in converter topology. SMC in its form of control directs paths of signals onto a surface, commonly referred to as the sliding surface or hyperplane. The sliding surface or hyperplane, allows a control signal to direct trajectory points. In this paper, a current-mode control is adopted. The configuration of the sliding mode controller is robust amplitude modulated. The small-signal modelling analysis was done to equalize and mathematically derive the system parameters due to its non-linearities, verified through simulation and experimental results.